Analisis Pengguna Kereta Api Jabotabek Ekonomi Terhadap Tingkat Pelayanan Stasiun Kereta Api Jakarta – Kota - Arris Maulana; Lies Indriyati (LOGISTIK, 2008)
This writing aims to detect economy train user characteristics jabotabek based on from economy social aspects with detect how far service level that given by side PT. Train (share) as according to standard transport service level at urban affairs. writing method that used in task writing ends this approach primary data shaped survey at field with takes sample from a population and use kuesioner as a means of primary data collectors, and wear literature method with comparison percentage. from primary data result hits economy train user characteristics jabotabek based on from economy social aspects and service level that given by side pt. train (share) daop 1 jakarta can at conclude that economy train service user characteristics jabotabek based on from economy social aspects, a large part this service user private official or bumn (54.3%) and entrepreneur or tradesman (14.3%) berpenghasilan intermediate downwards. with minimal education level sltp (8.6%), slta (48.6%) and do trip quantity as much as 1 (40%) or 2 (34.3%) times with need to work and expense. To overcome troubleshoot suggested need repair significant especially from cleanliness aspect, security, and freshment in station. add train occupant railway carriage series total and repair performance train operators.